Single‐dose administration of clenbuterol is detectable in dried blood spots. Issue 9 (20th June 2020) - Solheim, Sara Amalie; Jessen, Søren; Mørkeberg, Jakob; Thevis, Mario; Dehnes, Yvette; Eibye, Kasper; Hostrup, Morten; Nordsborg, Nikolai Baastrup
Abstract: Clenbuterol is a β2 ‐agonist prescribed for asthmatic patients in some countries. Based on its anabolic and lipolytic effects observed in studies on rodents and in livestock destined for food production, clenbuterol is abused by bodybuilders and athletes seeking leanness. Urinary clenbuterol analysis is part of routine doping analysis. However, the collection of urine samples is time‐consuming and can be intimidating for athletes. Dried blood spot (DBS) appears attractive as an alternative matrix, but the detectability of clenbuterol in humans through DBS has not been investigated. This study evaluated if clenbuterol could be detected in DBS and urine collected from six healthy men after oral intake of 80 μg clenbuterol. The DBS and urine samples were collected at 0, 3, 8, 24, and 72 h post‐ingestion, with additional urine collections on days 7 and 10. Using LC–MS/MS, it was shown that clenbuterol could be detected in all DBS samples for 24 h post‐ingestion and with 50% sensitivity 3 days after ingestion. The DBS method was 100% specific. Evaluation of analyte stability showed that clenbuterol is stable in DBS for at least 365 days at room temperature when using desiccant and avoiding light exposure. In urine, clenbuterol was detectable for at least 7–10 days after ingestion. Urinary clenbuterol concentrations below 5 ng/mL were present in some subjects 24 h after administration. Collectively, these data indicate that DBS are suitable for routine doping control analysis of clenbuterol with a detection window of at least 3 days after oral administration of 80 μg. Abstract : Dried blood spots (DBS) is a faster and less intrusive sample collection method than urine, but the detectability of clenbuterol in human DBS following clenbuterol ingestion is unexplored. It was shown that clenbuterol is detectable in DBS for at least 3 days post‐ingestion of a single dose of 80 μg clenbuterol in some individuals, with 100% specificity. Thus, DBS appears to be an applicable sample matrix for use in doping control and analysis.